Modified semitendinosus muscle transposition to repair ventral perineal hernia in 14 dogs. (3rd March 2015) - Morello, E.; Martano, M.; Zabarino, S.; Piras, L. A.; Nicoli, S.; Bussadori, R.; Buracco, P.
<x xml:space="preserve">Abstract</x> OBJECTIVES To describe a modified technique of semitendinosus muscle transposition for the repair of ventral perineal hernia. MATERIALS AND METHODS Retrospective review of case records of dogs with ventral perineal hernia that were treated by transposing the medial half of the longitudinally split semitendinosus muscle of one limb. The transposition of the internal obturator muscle was used when uni‐ or bilateral rectal sacculation was also present in addition to ventral perineal hernia; colopexy and vas deferens pexy were also performed. RESULTS Fourteen dogs were included. In addition to ventral perineal hernia, unilateral and bilateral perineal hernia was also present in five and six of the dogs, respectively. The mean follow‐up time was 890 days. Ventral perineal hernia was successfully managed by the modified semitendinosus muscle transposition with minor complications in all the dogs included in the study. CLINICAL SIGNIFICANCE Despite the small number of dogs included, the unilateral transposition of the medial half of the longitudinally split semitendinosus muscle consistently supported the ventral rectal enlargement in perineal hernia without obvious adverse effects.